Inhibitory Effect of Nelumbo nucifera Leaf Extract on 2-Acetylaminofluorene-induced Hepatocarcinogenesis Through Enhancing Antioxidative Potential and Alleviating Inflammation in Rats - Mon-Yuan Yang; Tung-Wei Hung; Chau-Jong Wang; Tsui-Hwa Tseng (MDPI AG, 2019)
Leaf extract of Nelumbo nucifera (NLE) has been demonstrated to possess anti-atherosclerosis, improve alcohol-induced steatohepatitis, prevent high-fat diet-induced obesity, and inhibit the proliferation and metastasis of human breast cancer cells. This study determines the chemopreventive role of NLE against 2-acetylaminofluorene (AAF)-induced hepatocellular carcinoma (HCC) in rats. AAF was used to induce hepatocarcinogenesis in rats through genetic and nongenetic effects. After administration for 12 weeks, NLE (0.5−2%) supplementation orally inhibited AAF (0.03%)-induced hepatic fibrosis which appears during the development of premalignant lesions in rats. After the 6-month experiment, NLE supplementation resulted in decreasing AAF-induced serum parameters of hepatic injury, including the level of triglycerides, total cholesterol, alpha-fetoprotein (AFP), and inflammatory mediator interleukin (IL)-6 and tumor necrosis factor (TNF)-α as well as the activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and gamma-glutamyl transferase (γGT). NLE supplementation also reduced AAF-induced lipid peroxidation and 8-hydroxy-2′-deoxyguanosine (8-OHdG) formation in the rat liver. Hepatic histopathological investigation revealed that NLE supplementation attenuated the AAF-induced HCC and glutathione S-transferase-Pi (GST-Pi) expression. Furthermore, NLE supplementation increased the expression of transcription factor, nuclear factor erythroid 2-related factor 2 (Nrf2) and its downstream targets, including catalase, glutathion peroxidase (GPx), and superoxide dismutase 1 (SOD-1) in the rat liver. Our findings indicate that NLE supplementation inhibited AAF-induced hepatocarcinogenesis by enhancing antioxidative potential and alleviating inflammation in rats.